2007
DOI: 10.1002/adma.200700082
|View full text |Cite
|
Sign up to set email alerts
|

Biospecific Recognition of Tethered Small Molecules Diluted in Self‐Assembled Monolayers

Abstract: A model system for the capture of large biomolecule targets by small-molecule probes has been developed using a combination of insertion self-assembly and chemical functionalization. Key to selective molecular recognition of small molecules is the ability to tether these such that they are readily accessible for binding. This is particularly challenging because the tether alters a significant fraction of the probe molecule. It is also critical to space small-molecule probes so that they are dilute and exposed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
112
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(114 citation statements)
references
References 30 publications
2
112
0
Order By: Relevance
“…It is important to note that in the overlapping patterned regions, the tether molecules (which are functionalized with smallmolecule probes) are isolated such that they do not interact with other probe molecules in the surrounding region. This molecular isolation can be controlled and influenced by many factors and has been confirmed by both ensemble and localized analytical techniques (Mullen et al 2007a;Shuster et al 2008).…”
Section: Chemically Patterned Surfacesmentioning
confidence: 69%
See 3 more Smart Citations
“…It is important to note that in the overlapping patterned regions, the tether molecules (which are functionalized with smallmolecule probes) are isolated such that they do not interact with other probe molecules in the surrounding region. This molecular isolation can be controlled and influenced by many factors and has been confirmed by both ensemble and localized analytical techniques (Mullen et al 2007a;Shuster et al 2008).…”
Section: Chemically Patterned Surfacesmentioning
confidence: 69%
“…A patterned elastomeric stamp coated with the molecules to be patterned is brought into contact with a substrate coated with a preexisting monolayer that is not easily displaced; the molecules on the stamp insert into the defects in the preexisting monolayer where the stamp and substrate are in contact. Schematics are not to scale terminal functionalities from the preexisitng SAM are inserted into its defect sites (Weck et al 1999;Mullen et al 2007b;Shuster et al 2008). Subsequently, the terminal groups of the tether molecules are functionalized with small-molecule ligands.…”
Section: Chemically Patterned Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 Insertion also prevents phase separation. 23,30À33 A recent study of DNA hybridization on Au electrodes demonstrated that surface hybridization was reduced because DNA probes tended to aggregate into domains after backfilling with alcoholterminated alkanethiols. 34 In contrast, tethered DNA molecules inserted into defect sites in preformed SAMs produced dilute coverage wherein individual probe strands were isolated from each other.…”
mentioning
confidence: 99%